In vitro color change of three dental veneering resins in tea, coffee and tamarind extracts - J.K. Subramanya; S. Muttagi (Tehran University of Medical Sciences, 2011)
Objective: To study the in vitro color changes of three dental resin veneering materials when immersed in tea, coffee and tamarind extracts. Materials and Methods: The color changes of heat polymerized tooth colored acrylic resin (Stellondetrey, B, F14, DPI Dental products of India Ltd, Mumbai), auto polymerized tooth colored acrylic resin (DPI, B, QV5, DPI Dental products of India Ltd, Mumbai) and light polymerized resin composite (Herculite XRV, Enamel A2, part no. 22860, lot no. 910437, Kerr Corporation, West Collins Avenue, Orange, CA, USA) when immersed in water extracts of tea (Tata Tea Ltd. Bangalore, India), coffee (Tata Coffee Ltd. Coorg, India) and tamarind were evaluated using computer vision systems. The color images were recorded in R (red), G (green) and B (blue) form and converted into H (hue), S (saturation) and V (value). Results: Significant color change occurred for auto polymerized tooth colored acrylic resin in tamarind extract, for heat polymerized tooth colored acrylic resin in tea extract and for light polymerized resin composite in coffee extract. Auto polymerized tooth colored acrylic resin samples showed an overall higher color change. However, for all the material samples coffee extract produced more color change. Conclusion: These results suggest that the color stability of the resins is influenced by the presence of secondary metabolites such as tartaric acid, tannins, caffeine, saponins and phenols in tamarind, tea and coffee extracts.